2014
DOI: 10.1007/s00232-014-9726-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pathogenic Mutations on the Energetics of Translocon-Mediated Bilayer Integration of Transmembrane Helices

Abstract: Aberrant protein folding and assembly contribute to a number of diseases, and efforts to rationalize how pathogenic mutations cause this phenomenon represent an important imperative in biochemical research. However, for α-helical membrane proteins, this task is complicated by the fact that membrane proteins require intricate machinery to achieve structural and functional maturity under cellular conditions. In this work, we utilized the ΔG predictor algorithm (www.dgpred.cbr.su.se) to survey 470 known pathogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…Previously reported motor nerve conduction velocities of patients harboring these mutations confirm that the degree of dysmyelination caused by these mutations is highly variable ( Supplementary Table 1 ), which suggests that this set of mutations is likely to manifest a range of effects on the conformational equilibrium of PMP22. Additionally, we recently found that none of these mutations are predicted to cause topogenic defects, 23 which suggests that conformational defects are manifested after PMP22 is cotranslationally inserted into the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Previously reported motor nerve conduction velocities of patients harboring these mutations confirm that the degree of dysmyelination caused by these mutations is highly variable ( Supplementary Table 1 ), which suggests that this set of mutations is likely to manifest a range of effects on the conformational equilibrium of PMP22. Additionally, we recently found that none of these mutations are predicted to cause topogenic defects, 23 which suggests that conformational defects are manifested after PMP22 is cotranslationally inserted into the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Even single mutations to an IMP amino-acid sequence can disrupt integration and induce disease phenotypes [16] or decrease protein expression [1719]; similarly, mutations to the translocon channel can inhibit IMP folding [8, 2023]. The important role for IMPs in cellular functions, such as signal transduction, the transport of nutrients, and cell adhesion, motivates the understanding of the effect of NC and translocon properties on the efficiency of co-translational integration.…”
Section: Introductionmentioning
confidence: 99%
“…Establishing the principles governing the folding of a membrane protein is central to understanding the molecular basis for membrane proteins that display multiple topologies and a wide spectrum of membrane protein conformational and topological disorders (1)(2)(3)(4)(5)(6). At least 10% of 470 known pathogenic mutations were predicted to result in a change in the topological organization of the mutant membrane protein (7). A fundamental objective in membrane biology is to understand and predict how protein sequence determines the number and orientation of transmembrane domains (TMDs) 3 (8).…”
mentioning
confidence: 99%